Detail design of waste plastic bottles rescue boat - Law, Xue Ni (2012)
The increasing numbers of waste plastic bottles over the years has create environment issue across the world. By using the waste plastic bottles to arrange at the waterline section of a boat not only to instill the awareness regarding environment issue, but enhance the safety of the boat. Obviously, a fiberglass boat has the tendency to crack during the hit by the heavy wave or accidents. Hence, the wasted plastic bottles filled inside the rescue boat could act as a floating object to support the rescue boat for a while and avoid the boat to sink directly. Despite of the arrangement of bottles in the boat is major objective in the thesis; the design of general arrangement of the boat behaves as a part of objectives. The design of general arrangement is followed the Safety Of Life At Sea (SOLAS) regulations and several analyses on the design have been made to show the compatible of the design. The methodology utilized in this project from the design software to lines plan and general arrangement of rescue boat. From the result, the total displacement of rescue boat is 868.7kg including six people with an average weight of 100kg. The total wasted plastic bottles used are 332 with a total weight of 13.12kg. If the leaking problem occurs, the bottles are able to support 56% of buoyancy from the total weight. The design of the general arrangement is also consider the weigh distribution of a boat. The passenger seat is concentrated at the middle of the boat to maintain the stability of the rescue boat.